Optimization of Nitration of 3-Hydroxypyrazine-2-Carboxamide to 3-Hydroxy-6-Nitropyrazine-2-Carboxamide - Widiastuti Agustina Eko Setyowati; Ihsanawati Ihsanawati; Anita Alni (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
This study focuses on optimizing the synthesis of 3-hydroxy-6-nitropyrazine-2-carboxamide, a critical intermediate in producing various pyrazine-based pharmaceuticals. The compound is synthesized through the nitration of 3-hydroxypyrazine-2-carboxamide, employing sulfuric acid (H2SO4) and potassium nitrate (KNO3) as reagents. The research aimed to refine the synthesis process to enhance yield purity for pharmaceutical applications. The optimization entailed adjusting the reagents' composition and solvents, specifically the ratio of substrate to KNO3, the volume of H2SO4 used per gram of substrate, and the temperatures for both the reaction and product precipitation. Optimal results were observed at a substrate-to-KNO3 ratio of 1:2, with 12 mL of H2SO4 per gram of substrate. The reaction temperature was set at 50°, and precipitation occurred effectively at 0°C. This optimized method significantly improved the yield and purity of the compound. The process demonstrated excellent repeatability, with yields ranging from 77% to 80%, a considerable increase from the 48% yield reported in previous studies. The molecular structure of the synthesized compound was confirmed through comprehensive spectroscopic analyses, including 1H NMR, 13C NMR, and High-Resolution Electrospray Ionization Time-of-Flight Mass Spectrometry (HRESI-TOF-MS). This research represents a significant advancement in synthesizing 3-hydroxy-6-nitropyrazine-2-carboxamide, offering a more efficient and reliable method for producing this key pharmaceutical intermediate. The improved synthesis process ensures higher yields and maintains the purity required for pharmaceutical applications, thereby contributing to the efficient development of pyrazine-based drug compounds.